Conformation of HLA-E/peptide complex guides interaction with two novel HLA-E receptors: Stabilin 1 and 2 - Tom A. W. Schoufour; Linda Voogd; Kees L.M.C. Franken; Tom H.M. Ottenhoff; Ruud H.M. Wijdeven; Simone A. Joosten (PLoS ONE, 2025)
Human leukocyte antigen E (HLA-E) communicates cellular health to natural killer (NK) cells through presentation of peptides derived from the leader sequence of classical major histocompatibility complex class I (MHC-I), inhibiting NK cell activation and lysis of healthy cells. Besides this canonical role, HLA-E can also present peptides from pathogens such as Mycobacterium tuberculosis (Mtb) to T cells and can inhibit phagocytosis by engaging with LILRB1/2. To identify additional HLA-E binding surface molecules, we utilized a CRISPR/Cas9 activation screen with HLA-E tetramers, which identified Stabilin (STAB)1 and STAB2 as novel interactors. This interaction depended on the nature of the peptide/HLA-E complex, whereby high affinity peptides did not permit the interaction while low affinity peptides did. Functionally, expression of STAB1 or STAB2 on THP-1 monocytes increased phagocytic uptake of HLA-E coated microbeads. These results provide the first evidence of an interaction between Stabilin receptors and specific HLA-E conformations.